Overexpression of the Matrix Metalloproteinase Matrilysin Results in Premature Mammary Gland Differentiation and Male Infertility - Rudolph-Owen, Laura A. (The American Society for Cell Biology, 1998)
To examine the role of matrilysin (MAT), an epithelial cell-specific matrix metalloproteinase, in the normal development and function of reproductive tissues, we generated transgenic animals that overexpress MAT in several reproductive organs. Three distinct forms of human MAT (wild-type, active, and inactive) were placed under the control of the murine mammary tumor virus promoter/enhancer. Although wild-type, active, and inactive forms of the human MAT protein could be produced in an in vitro culture system, mutations of the MAT cDNA significantly decreased the efficiency with which the MAT protein was produced in vivo. Therefore, animals carrying the wild-type MAT transgene that expressed high levels of human MAT in vivo were further examined. Mammary glands from female transgenic animals were morphologically normal throughout mammary development, but displayed an increased ability to produce β-casein protein in virgin animals. In addition, beginning at approximately 8 mo of age, the testes of male transgenic animals became disorganized with apparent disintegration of interstitial tissue that normally surrounds the seminiferous tubules. The disruption of testis morphology was concurrent with the onset of infertility. These results suggest that overexpression of the matrix-degrading enzyme MAT alters the integrity of the extracellular matrix and thereby induces cellular differentiation and cellular destruction in a tissue-specific manner.